Technological change and the environmental imperative challenges to the copper industry - Brundenius, Claes, 1938-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2003)
Technological Change and the Environmental Imperative considers the extent of the success of polluting industries in becoming cost-efficient whilst acquiring less polluting technologies, in the face of fierce competition. The authors also discuss what has been the impact of privatisation on this process and what lessons have been learnt. Against this backdrop, and drawing on case material from Chile, China, Peru and Russia, the book goes on to assess the latest technological breakthroughs, and their possible future impact on cost efficiency and the environment.
Economic liberalization, innovation and technology transfer : opportunities for cleaner production in copper mining and processing / Alyson Warhurst and Gavin Bridge -- Technological change and the environmental imperative in Chile : challenges to the largest copper producer in the world / Claes Brundenius -- Technological change and the environmental imperative : the case of copper smelting in China / Bo Göransson -- From nationalization to re-privatization of the Peruvian copper industry : structural changes and impact on environmental sustainability / Claes Brundenius -- Growth, competitiveness and sustainability : technological change in the Russian copper industry / Boris Kuznetsov and Igor Budanov -- Flash technology facing the challenges of the third millennium / Pekka Hanniala and Ilkka V. Kojo.
Includes bibliographical references and index.
Keywords: Copper industry and trade -- Environmental aspects -- Developing countries; Copper industry and trade -- Technological innovations; Electronic books